Therapy of Dredging the Bowels Enhanced the Neuroprotective Effect of Nourishing Kidney Herbs on Hippocampal Cholinergic System in Alzheimer's Disease Model Rat Induced by Aβ 1-42. (12th September 2018) - Feng, Lu-Da; Tian, Yang; Wang, Xin; Dai, Run; Cai, Song; Cao, Yu-Jia; Si, Yin-Chu
Abstract : Background. Therapy of nourishing kidney has been used for treating memory deficits of Alzheimer's disease (AD) for thousands of years based on traditional Chinese medicine. However, we found the therapy of dredging the bowels could alleviate both memory deficits and mental symptoms of AD in clinic. Objective . To determine whether the therapy of dredging the bowels could enhance the neuroprotective effect of nourishing kidney herbs for treating AD rats, and to explore the underlying mechanism of the combination of nourishing kidney and dredging the bowels (NKDB) herbs. Methods . 60 rats were randomly divided into sham-operated group (SOG), model group (MG), nourishing kidney group (NKG), dredging the bowels group (DBG), nourishing kidney and dredging the bowels group (NKDBG), and donepezil hydrochloride group (DHG). The model establishment was performed by injecting A β 1-42 into the hippocampal CA1 region. Animals received aqueous solution of Chinese herbal medicine or western medicine while SOG received only distilled water. Ability of learning and memory were assessed by Morris water maze. Acetylcholinesterase(AChE) and choline acetyltransferase (ChAT) activity and positive cells in the hippocampus were detected by the biochemical and immunofluorescent assay. Results . All rats were in the same baseline. While after model establishment, ability of learning and memory of MG, NKG, DBG, NKDBG, and DHG were significantly impaired compared with SOG. Whereas after treatment, ability of learning and memory of NKG, DBG, NKDBG, and DHG were significantly improved compared with MG. Additionally, AChE activity of NKG, DBG, and NKDBG was significantly decreased, meanwhile ChAT activity showed an increased tendency. The number of AChE-positive cells and ChAT-positive cells of both NKDBG and DHG were significantly decreased and increased respectively, superior to those when compared with NKG and DBG. What's more, there was no significant difference between NKDBG and DHG. Conclusion . Therapy of dredging the bowels could enhance the neuroprotective effect of nourishing kidney herbs by reversing morphological damage of hippocampal cholinergic system. Furthermore, treatment with NKDB herbs could be effectively against AD, providing a practical therapeutic strategy in clinic.